2021
DOI: 10.3390/brainsci11050585
|View full text |Cite
|
Sign up to set email alerts
|

Perseverative Cognition in the Positive Valence Systems: An Experimental and Ecological Investigation

Abstract: Perseverative cognition (PC) is a transdiagnostic risk factor that characterizes both hypo-motivational (e.g., depression) and hyper-motivational (e.g., addiction) disorders; however, it has been almost exclusively studied within the context of the negative valence systems. The present study aimed to fill this gap by combining laboratory-based, computational and ecological assessments. Healthy individuals performed the Probabilistic Reward Task (PRT) before and after the induction of PC or a waiting period. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Our findings support the application of the tripartite theory to cognitive risk for depression in RNT and rumination manifesting in specifically lower levels of day-to-day PA compared to worry and anxiety sensitivity. Additionally, one recent study that measured perseverative cognition, a construct encompassing both negatively and positively valenced repetitive thought, and reward processing in daily life found that momentary RNT predicted reduced reward satisfaction (a construct tied to diminished PA) after consuming the reward (Schettino et al, 2021). While Schettino et al, did not explicitly measure momentary PA, their study lends further ecological validity to the relationship between RNT and positive emotion found here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings support the application of the tripartite theory to cognitive risk for depression in RNT and rumination manifesting in specifically lower levels of day-to-day PA compared to worry and anxiety sensitivity. Additionally, one recent study that measured perseverative cognition, a construct encompassing both negatively and positively valenced repetitive thought, and reward processing in daily life found that momentary RNT predicted reduced reward satisfaction (a construct tied to diminished PA) after consuming the reward (Schettino et al, 2021). While Schettino et al, did not explicitly measure momentary PA, their study lends further ecological validity to the relationship between RNT and positive emotion found here.…”
Section: Discussionmentioning
confidence: 99%
“…Composite PA and NA scores were computed by taking the average of the PA and NA items endorsed at each survey prompt. Multilevel reliabilities were estimated for PA and NA using the lavaan (Rosseel et al, 2019) and semTools (Jorgensen et al, 2022) packages in R. Cronbach's alpha was computed at the within-and between-person levels separately. We found that within-person reliability for PA and NA were acceptable (aPA = .70; aNA = .76), and between-person reliability for PA and NA was very good (aPA = 93; aNA = .88).…”
Section: Ecological Momentary Assessment Surveymentioning
confidence: 99%
“…To this end, Schettino and colleagues focus on perseverative cognition, a form of cognition that is characterized by repetitive, intrusive and negative thoughts and has been linked to depression and anxiety. By combining laboratory-based reward tasks, computational modelling and ecological assessments in daily life, the authors demonstrate, for the first time, that perseverative cognition is also associated with abnormalities in the functionality of positive valence systems [ 1 ]. Another example stems from the study of Saporta and colleagues that focuses on loneliness.…”
mentioning
confidence: 99%